Retrospective radiological assessment of root canal treatment in young permanent dentition in a Turkish subpopulation - NAMDAR PEKİNER, FİLİZ MEDİHA (WILEY, 2011)
Gumru B, Tarcin B, Pekiner FN, Ozbayrak S. Retrospective radiological assessment of root canal treatment in young permanent dentition in a Turkish subpopulation. International Endodontic Journal, 44, 850-856, 2011. Aim To determine the technical quality of root fillings as well as the periapical status of root filled teeth and non-root filled teeth in young permanent dentitions using a retrospective analysis of orthopantomographs (OPTGs) in a Turkish subpopulation. Methodology Included in this study were the digital OPTGs taken as a part of diagnostic and planning procedures for all 19-year-old adolescents who attended the Faculty of Dentistry, Marmara University (Istanbul, Turkey) for the first time during the period from June 2007 to May 2009. The periapical status of all teeth and the technical quality of the root fillings were assessed by radiographic criteria. Statistical analysis was performed by the Mann-Whitney U, chi-squared, Fisher's exact and Cohen's kappa tests. Results The survey involved OPTGs of 1077 19-year-old adolescents: 663 (61.6%) women and 414 (38.4%) men. Of the 28974 teeth examined, 459 (1.6%) were root filled, of which 193 (42.0%) had radiological signs of apical periodontitis (AP), and 454 (1.6%) were non-root filled teeth with AP. No significant difference was found between women and men regarding the number of teeth present, the number of root filled teeth and the number of non-root filled teeth with AP (P > 0.05). The most commonly treated teeth were molars (54.2%), followed by pre-molars (27.0%) and incisors (18.8%). Length was adequate in 57.3%, and homogeneity was adequate in 50.5% of the root fillings. Statistically, both the length and the homogeneity of the root fillings were significantly associated with periapical status individually (P < 0.01). The overall technical quality was inadequate in 60.1% of the root fillings, and 67.0% of these were associated with signs of AP. Amongst root filled teeth, the frequency of AP in connection with molars was significantly higher (57.0%) than that for incisors (27.9%) and pre-molars (21.8%) (P < 0.01). Conclusions The results of this study indicated that the frequency of root filled teeth with AP, non-root filled teeth with AP and of technically inadequate root fillings amongst all root filled teeth was high in this selected adolescent Turkish population.
Keywords: apical periodontitis; endodontics; epidemiology; radiology; root canal treatment; ENDODONTICALLY TREATED TEETH; ADULT SPANISH POPULATION; PERIAPICAL STATUS; APICAL PERIODONTITIS; FILLED TEETH; CORONAL RESTORATIONS; TECHNICAL QUALITY; RADIOGRAPHIC EVALUATION; DANISH POPULATION; PREVALENCE